Early Functional Mutants of Coliphage λ - Naha, P. M. (1967)
The early functional mutants of λ, belonging to cistrons N, O, and P, are known to be blocked prior to vegetative multiplication of the λ genome. Superinfection of heteroimmune defective lysogens by these mutants failed to elicit the function required for replication of the superinfecting phage. The mutants among themselves also showed poor cooperation on a nonpermissive host. Studies on the effects of different multiplicities of infection for bacterial lysis showed identical responses for mutants of different cistrons.